KEMAMPUAN MENULIS PUISI BERIMA SISWA KELAS X SMA BRAWIJAYA SMART SCHOOL - Wicaksana, Andrean (Hasta Wiyata, 2023)
ABSTRACTThe ability to write rhyming poetry is one of the studies that describes the ability to write poetry using the poetry rhyme method. This is important because based on observations, students' poetry writing skills are considered lacking. This study aims to determine: 1) the ability to write rhyming poetry in class X SMA Brawijaya Smart School Malang in terms of sound; 2) the ability to write rhyming poetry for students of class X SMA Brawijaya Smart School Malang in terms of word position. The design used in this research is descriptive quantitative which describes the variables in the form of numbers or statistics obtained from the results of a written test which is a description of the ability of class X students of SMA Brawijaya Smart School Malang in writing a rhyming poem. The data in this study were analyzed through five stages, namely data, data identification, data classification, data analysis, and drawing conclusions. The results of data processing in this study enjoyed that the ability of class X students of SMA Brawijaya Smart School Malang in writing rhyming poetry was sufficient. Based on the results of data processing, it appears that the test results of class X students of SMA Brawijaya Smart School Malang in writing rhyming poetry are in the good category with an average value of 88.Â